Analisis Kecerdasaran Spiritual, Stress Kerja dan Kesehatan Mental - Alias Arif Likoi; Prancis Hutabarat; Ronny Sihotang (Journal of Management and Bussines (JOMB), 2024)
This research aims to examine the relationship between spiritual intelligence and work stress and mental health in the work environment, amidst challenges such as the ongoing pandemic and the threat of global inflation. This study uses questionnaire methods and PLS-SEM analysis to test hypotheses, considering the speculative nature of this research which focuses on estimating key factors that determine mental health. Analysis was carried out with SmartPLS 3.0 software. The research results show that companies need to pay attention to the health of their employees, including mental health, because work stress has been proven to be a significant factor in influencing mental health. However, research finds that spiritual intelligence does not have a significant influence on mental health or work stress. In conclusion, companies must focus more on efforts to reduce work stress to improve employee mental health, because this factor has a significant impact. Meanwhile, spiritual intelligence has not been proven to be influential in this context, so companies can direct their efforts mainly on other aspects that are more relevant to employee mental health. Keywords: Spiritual Intelligence, Mental Health, Work Stress